2003
DOI: 10.2337/diabetes.52.9.2411
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Cathepsin L Gene Expression in Skeletal Muscle Is Associated With Type 2 Diabetes

Abstract: To identify abnormally expressed genes associated with muscle insulin resistance or type 2 diabetes, we screened the mRNA populations using cDNA differential display combined with relative RT-PCR analysis from muscle biopsies of diabetes-prone C57BL/6J and diabetes-resistant NMRI mice fed with a high-fat or normal diet for 3 or 15 months. Six abnormally expressed genes were isolated from the mice after a 3-month fat feeding; one of them was cathepsin L. No significant difference in mRNA levels of these genes w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 46 publications
(52 reference statements)
2
18
0
1
Order By: Relevance
“…In the skeletal muscle of diabetic subjects, reduced insulin-stimulated cathepsin L gene expression was also reported in this paper, suggesting that impaired cathepsin L expression is secondary to impaired glucose metabolism [214]. Cathepsin S levels strongly correlate with insulin resistance as reported by Jobs and coworkers, who in their study showed that subjects with higher cathepsin S levels had decreased insulin sensitivity and higher risk to develop type 2 diabetes [215].…”
Section: Role Of Proteases In Cardiometabolic Diseasessupporting
confidence: 71%
See 1 more Smart Citation
“…In the skeletal muscle of diabetic subjects, reduced insulin-stimulated cathepsin L gene expression was also reported in this paper, suggesting that impaired cathepsin L expression is secondary to impaired glucose metabolism [214]. Cathepsin S levels strongly correlate with insulin resistance as reported by Jobs and coworkers, who in their study showed that subjects with higher cathepsin S levels had decreased insulin sensitivity and higher risk to develop type 2 diabetes [215].…”
Section: Role Of Proteases In Cardiometabolic Diseasessupporting
confidence: 71%
“…Expression levels of cathepsin L in the muscle has been shown to be elevated in glucose intolerant mice [214]. In the skeletal muscle of diabetic subjects, reduced insulin-stimulated cathepsin L gene expression was also reported in this paper, suggesting that impaired cathepsin L expression is secondary to impaired glucose metabolism [214].…”
Section: Role Of Proteases In Cardiometabolic Diseasessupporting
confidence: 64%
“…Although previous reports indicate that MMPs may be a responsible enzyme for this as discussed below, our results demonstrate cathepsin L, which can generate endostatin from collagen XVIII (12), may also play a role in the differential expression of endostatin observed. Other investigators have demonstrated that cathepsin activity is altered in the setting of diabetes (20,24). Reddy et al (36) have shown collagen breakdown is differentially regulated between diabetic and nondiabetic subjects.…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies have suggested that IRS-1 can be regulated at the transcriptional level Molloy et al, 2000;Huang et al, 2002). MCF-7 cells were treated with 10 mM RA for 24, 48 and 72 h, total RNA was extracted and IRS-1 mRNA expression was examined by Northern blot, wherein the 8.5 kb transcript is shown (Figure 2a, top panel).…”
Section: Ra Induces a Post-translational Modification Of Irs-1 In Mcfmentioning
confidence: 99%